DEVIANT BEHAVIOR: PSYCHOLOGICAL PREVENTION AND PSYCHOLOGICAL INTERVENTION (Proceedings of the World Disability & Rehabilitation Conference, 2019)
The purpose of the study is to carry out a retrospective analysis of the basic concepts, theoretical approaches to the prevention and correction of deviant behavior that exists in modern psychology. The main method of the research is a retrospective analysis of the literature. This study shows the direction of social and psychological care for adolescents with deviant behavior which include prevention (warning, cautioning) and intervention (overcoming, correction, and rehabilitation). In conclusion, various social institutions regulate deviant behavior of an individual. Public exposure may have the character of legal sanctions, medical treatment, social support and psychological assistance. Due to the complex nature of behavioral disorders their prevention requires overcoming an organized system of social and psychological influences. Psychological prevention and intervention are seen as areas of rehabilitation, correctional and correctional-educational work with individuals who have behavioral problems, the main purpose of which is to overcome the disorders of mental development. Implementation of effective psychological prevention and correction of deviant behavior of a person occurs only when a person turns it into operation, when a person makes a personal choice, sets new goals. In order to overcome the deviant behavior, people should be able to make choices, to assess the consequences of the decisions to regulate emotional processes accompanying behavior, i.e. to organize their own livelihoods with generally accepted norms, which ultimately helps to reduce existing strains of personality as well as its active socialization.
Keywords: Deviant behavior; psychological prevention; psychological intervention